Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

Now sure how to get to answer: A quadratic function, f, has zeros P and Q such that P+Q=5 and (1/P)+(1/Q)=8. What function would best describes f?

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

so you have sum of roots find product of roots PQ from (1/P)+(1/Q)=8. can u ?
Okay so I assume I use substitution here?
you can, yes. but see this : 1/P + 1/Q =8 (Q+P)/PQ = 8 we know P+Q = 5 so, 5/(PQ) = 8 got this ?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

find PQ now
Hmm I think so. So PQ = 5/8 ?
yes.
now , equation will be \(x^2 -(P+Q)x + PQ = 0\)
then simplify
okay so 8x^2-40x+5, which I know is the right answer. I'm still a bit confused where "x^2−(P+Q)x+PQ=0" Is that a formula I forgot?
thats a standard relation. like if you have x^2 +ax+b = 0 sum of roots will be -a and product of roots = b thats where it came from
Oh yeah, I vaguely remember that. One more thing sorry, how difficult would the substitution be?
to find PQ ? not much, you can try
a longer way will be to actually find the values of P and Q. then equation will be (x-P)(x-Q) = 0 then simplify
\[f(x)=(x-P)(x-Q)\]is just the polynomial in factored form \[f(x)=(x-P)(x-Q) = x^2-Qx-Px+PQ = x^2-(P+Q)x + PQ\] after expansion and collecting like terms
Okay that makes a lot of sense. Was just blanking out there. Thanks for the help guys!
and substitution isn't too bad: \[P+Q=5\]\[P=5-Q\]\[\frac{1}P+\frac{1}Q =8\]\[\frac{1}{5-Q}+\frac{1}Q =8\]Multiply everything by \(Q(5-Q)\) to get \[Q+5-Q = 8Q(5-Q)\]\[-8Q^2+40Q-5=0\]Etc.
I still like @hartnn's approach best, though
Thanks again, really helped clear it up.

Not the answer you are looking for?

Search for more explanations.

Ask your own question